P113 Adverse childhood experiences and life course trajectories of anxiety and depression: the role of education. (13th September 2016) - Thompson, EJ; Richards, M; Gaysina, D
Abstract : Background: In a recent systematic review and meta-analysis of prospective longitudinal studies we conducted, specific types of adverse childhood experiences (ACEs), and multiple ACEs (3+), were found to be significantly associated with internalising symptoms in adulthood. There is evidence that these associations depend on the presence of subsequent adult factors, such as education. Methods: We used data from the Medical Research Council National Survey of Health and Development (NSHD) ( n = 5362). A wide range of prospectively measured ACEs were grouped into six domains: 'family instability', 'family socio-economic status', 'parental age', 'childrearing and parenting', 'parental health', and 'childhood health'. Multinomial logistic regressions and SEM were used to: 1) investigate associations between ACEs and different life course trajectories of internalising symptoms: absence of symptoms, adolescent symptoms with good adult outcome, adult onset symptoms, and adolescent onset repeated symptoms; and 2) to explore the role of educational level (degree or higher vs. no degree) by age 26, in the pathway between ACEs and life course trajectories of internalising symptoms. Results: ACEs across multiple domains were significantly associated with adolescent onset repeated symptoms (all ps < 0.05): number of residential moves (3+), OR = 1.38; father's occupation (manual), OR = 1.51; mother's perceived health (average with complaints/poor), OR = 1.23; birth weight (<2500 grams), OR = 1.92; and chronic childhood illness (yes), OR = 1.47. Two ACEs including number of residential moves, OR = 1.31; and mother's perceived health, OR = 1.42; were associated with adult onset symptoms. One ACE: birth weight (<2500 grams), OR = 2.04, was significantly associated with adolescent onset symptoms with a good adult outcome. Significant associations were found between ACEs and educational level at age 26: father's occupation (manual), OR = 0.13; and father's education (primary), OR = 0.15; cleanliness of house (average/among the least clean), OR = 0.27; mother's perceived health (average with complaints/poor), OR = 0.54; birth weight (<2500), OR = 0.49; childhood illness (yes), OR = 0.64, were negatively significantly associated with lower level of education. Lower level of education was significantly associated with adolescent onset repeated symptoms, OR = 1.54, and adolescent onset symptoms with good adult outcome, OR = 2.28. Conclusion: These preliminary results suggest that education may be a specific potentially modifiable pathway underling the association between ACEs and internalising symptoms.